God has No Favourites : The New Testament on First Century Religions - Scott, Basil (Book collections on Project MUSE., 2017)
"The New Testament does not conform neatly to any modern attempts to define the Christian approach to other religions, argues Basil Scott. He confronts the questions: What does the New Testament tell us about religions? And what is its approach to those who were Gentiles, and to their beliefs and practices? He focuses his attention on the evidence presented by the New Testament itself, and especially on the attitude of its writers to the religions of their times."--